A method for preparing a Pt-MOFs nanomotor and its coated suture for surgical wound infection monitoring

By coating Janus-type Pt-MOFs nanomotors synthesized by selective growth of Cu-MOFs on Pt nanobranches on medical sutures, the difficulties of surgical wound infection monitoring and prevention are solved, and bacterial imaging and antibacterial effects are achieved under inflammatory conditions.

CN118955927BActive Publication Date: 2025-04-15QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411027254.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-04-15
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively monitor and prevent surgical wound infections, and traditional monitoring methods are expensive and cannot meet the needs of surgical wound monitoring after discharge.

Method used

The Janus-type Pt-MOFs nanomotor synthesized by selective anisotropic growth on Pt nanobranches is used to coat the nanomotor on medical silk sutures, and the bacterial imaging and antibacterial properties under inflammatory conditions are used to achieve monitoring and prevention of surgical wound infection.

Benefits of technology

Pt-MOFs nanomotors show excellent bacterial imaging and antibacterial properties under inflammatory conditions, and can effectively monitor and prevent surgical wound infections, providing a new clinical practice strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955927B_ABST
    Figure CN118955927B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of surgical wound infection monitoring, and in particular to a Pt-MOFs nanomotor and coated suture for surgical wound infection monitoring and a preparation method thereof. It is prepared by selective anisotropic growth of Cu-based tetra(4-pyridylphenyl)ethylene (TPPE) nanoscale metal organic framework Cu-MOFs on Pt nanodendrites; the Pt nanodendrites are used as propulsion elements, and AIE luminescent prototype MOFs are used as fluorescence generating elements and antibacterial agents. The surface of the suture is coated with the above-mentioned Pt-MOFs nanomotor. The present invention is made by coating a janus-type nanomotor on a medical suture, and this nanomotor can improve the permeability of bacterial biofilms by self-propulsion, thereby enhancing the interaction between bacterial cells and antibacterial drugs. The Pt-MOFs nanomotor exhibits excellent therapeutic ability in accelerating wound healing, such as reducing inflammatory infiltration, enhancing collagen deposition, improving re-epithelialization and increasing CD31 expression, providing a new strategy for monitoring and treating surgical wound infections in clinical practice.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surgical wound infection monitoring, and in particular to a Pt-MOFs nanomotor and a coated suture thread for surgical wound infection monitoring and a preparation method thereof. Background Art

[0002] Currently, the main cause of surgical site infection is the widespread use of implanted materials during surgery. Medical sutures, as the most commonly used medical devices, can promote wound closure and healing, but their rough surfaces are likely to be attached by bacteria, leading to infection and inflammation. In clinical practice, the ability to monitor postoperative wounds remains a major challenge. Currently, surgical site infection (SSI) is the most common complication after surgical trauma. Due to its manifestation deep in the body, it is mainly detected by external signs such as skin color, body temperature and heart rate. However, the appearance of these indicators usually indicates that complications at the surgical site have become serious. Although more accurate assessments can be obtained through computed tomography, radiological examinations using ultrasound or fluoroscopy, these procedures are expensive and require specialized medical staff to perform. In addition, these clinical methods cannot meet the needs of monitoring surgical wounds after patients are discharged from the hospital.

[0003] In recent years, fluorescence technology has provided opportunities for monitoring bacterial infections directly from surgical sites due to its advantages of low interference, simple operation, good sensitivity and low cost. However, most traditional organic photosensitizers with strong π-π interactions suffer from aggregation quenching effects, which severely limits the scope of practical applications. The phenomenon of aggregation-induced emission (AIE) provides an effective solution to this problem. AIE refers to a unique intrinsic emission behavior in which fluorescent molecules emit weakly or not in dissolved solutions, but emit strongly in aggregates or solid states, which is caused by restricted intramolecular motion. This inherent property of AIE luminescent sources exhibits high fluorescence efficiency and photostability at high concentrations, revealing their potential in high-quality fluorescence imaging applications. Since most bacterial cell walls are rich in polysaccharides and peptidoglycans, AIE luminogens can easily aggregate to their surfaces through various non-covalent interactions, such as van der Waals interactions, electrostatic interactions, hydrophobic interactions and hydrogen bonding.

[0004] Surgical sutures offer an attractive and promising strategy for surgical wound infection monitoring due to their wide clinical applications and close integration with wound tissue. The development of advanced material modification and manufacturing technologies has resulted in a variety of monitoring sutures that can assess body physiological parameters in wound tissue. For example, multifilament surgical sutures functionalized with conductive polymers with capacitive sensors, flexible fibers for real-time monitoring of suture integrity, and hierarchical structural filaments integrating multiple clinically beneficial functions are described. However, although these surgical sutures can provide multiple data acquisition and flexible mechanics, the continuous suture technology and lack of antimicrobial activity limit their application in clinical monitoring of wound sites. Currently, with the rapid development of nanotechnology, which has become an integral part of modern medicine, it is possible to develop innovative sutures with certain predetermined properties, including wound monitoring, antimicrobial activity, and infection prevention. At the same time, the microenvironment of bacterially infected tissues exhibits different characteristics from healthy areas, including higher local temperature, hydrogen peroxide (H2O2), and the presence of a variety of bioactive substances. 2 O 2 ) overexpression, high glutathione (GSH) concentration, and acidic environment (pH 5.0-6.0). Therefore, there is an urgent need for a nanoparticle strategy that utilizes the infection microenvironment response to monitor and prevent the occurrence of surgical wound infection. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a Pt-MOFs nanomotor and a coated suture for surgical wound infection monitoring and a preparation method. By coating the medical silk suture with a janus-type nanomotor synthesized by selective anisotropic growth of Cu-MOFs on Pt nanobranches, the suture exhibits excellent bacterial imaging and antibacterial properties to different bacteria under inflammatory conditions, and has excellent surgical wound infection monitoring capabilities.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: a Pt-MOFs nanomotor for surgical wound infection monitoring is prepared by selective anisotropic growth of Cu-based tetra(4-pyridylphenyl)ethylene (TPPE) nanoscale metal organic framework Cu-MOFs on Pt nanodendrites;

[0007] The Pt nanodendrites serve as propulsion elements, and the AIE luminescent prototype MOFs serve as fluorescence generating elements and antibacterial agents.

[0008] By catalyzing H 2 O 2 The reduction of Cu-MOFs releases oxygen bubbles and exhibits the ability to self-propel in infected surgical wounds; in an acidic microenvironment, overexpressed GSH can drive the dissociation of copper ions in Cu-MOFs and the protonation of TPPE, causing TPPE to aggregate on the bacterial surface.

[0009] Preparation method of Pt-MOFs nanomotors for surgical wound infection monitoring,

[0010] (1) Synthesis of Pt nanodendrites;

[0011] (2) Synthesis of Pt-MOFs nanomotors:

[0012] PVP-stabilized Pt nanodendrites were added to CuSO 4 ·5H 2 O methanol solution, and stirred vigorously for 1h; 10mg, 0.15mmol TPPE was dissolved in a mixed solution of tetrachloroethylene and methanol, the volume ratio of tetrachloroethylene to methanol solution was 3:1, and then slowly added to the mixed solution prepared above, stirred at room temperature for 6 hours, the precipitate was centrifuged, washed with methanol to obtain Pt-MOFs nanomotors, and stored in deionized water.

[0013] Furthermore,

[0014] The synthesis steps of the Pt nanodendrites include:

[0015] H 2 PtCl 6 and PVP were dissolved in deionized water, and ascorbic acid solution was dropped into the mixed solution at room temperature. The mixed solution was heated to 45 °C and magnetically stirred at this temperature for 60 min, so that the color of the mixed solution changed from light yellow to black, indicating the synthesis of Pt nanodendrites.

[0016] Furthermore,

[0017] PVP-stabilized Pt nanodendrites in methanol and CuSO 4 ·5H 2 The volume ratio of O to methanol solution is 1:40;

[0018] CuSO 4 ·5H 2 The concentration of the methanol solution of O was 0.18 mol / L, and the concentration of the methanol solution of the pvp-stabilized Pt nanodendrites was 1.3 μM.

[0019] Furthermore,

[0020] H 2 PtCl 6 , the mass ratio of PVP and ascorbic acid is 8.2:1:17.5,

[0021] H 2 PtCl 6 The concentration of is 8.2 mg / ml, the concentration of PVP is 1 mg / ml, and the concentration of ascorbic acid is 35 mg / ml.

[0022] A Pt-MOFs nanomotor coated suture for surgical wound infection monitoring, wherein the surface of the suture is coated with the above-mentioned Pt-MOFs nanomotor.

[0023] Furthermore,

[0024] Sodium chloride solution was added to sodium alginate solution, stirred at room temperature overnight, Pt-MOFs nanomotor was added to the solution, and magnetic stirring was performed for 2 h to form alginate-Pt-MOFs nanomotor solution;

[0025] Will The silk suture was immersed in the alginate-Pt-MOFs nanomotor solution for 20 min and air-dried for 10 min. After repeating 10 times, the coated suture was immersed in CaCl 2 The sutures were cross-linked in the solution and immersed for 1 hour, washed with deionized water, and the cross-linked coated sutures were dried to obtain Pt-MOFs nanomotor coated sutures.

[0026] Furthermore,

[0027] The mass fraction of the sodium chloride solution is 0.1%, the mass fraction of the sodium alginate solution is 2%, and the volume ratio of the sodium chloride solution to the sodium alginate solution is 1:1.

[0028] Furthermore,

[0029] CaCl 2 The mass fraction of the solution is 4%.

[0030] The present invention is made by coating a janus-type nanomotor on a medical silk suture, which can improve the penetration of bacterial biofilms by self-propulsion, thereby enhancing the interaction between bacterial cells and antibacterial drugs. Pt-MOFs nanomotors show excellent therapeutic capabilities in accelerating wound healing, such as reducing inflammatory infiltration, enhancing collagen deposition, improving re-epithelialization and increasing CD31 expression, providing a new strategy for monitoring and treating surgical wound infections in clinical practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the formation and application of Pt-MOFs nanomotors in embodiments of the present invention: (a) Preparation process of Pt-MOFs nanomotors coated sutures; (b) Pt-MOFs nanomotors activated by infected microenvironments for bacterial monitoring and antibacterial activity.

[0032] Figure 2 Physical properties of the janus-type nanomotor according to the present invention: (a) and (b) TEM images of Pt nanodendrites; (c) Cu 2+TEM images of Pt-MOFs nanomotors with a molar ratio of (a) 1:0.5, (b) 1:1, (c) 1:1.5, and (d) 1:2. (g) DLS measurements of different Cu 2+ / TPPE molar ratio; (h) Zeta potential of Pt nanodendrites and Pt-MOFs nanomotors measured by DLS; (i) STEM-EDX elemental analysis of Pt-MOFs nanomotors, elemental maps corresponding to blue C, yellow Cu and pink Pt; (j) Different H 2 O 2 Motion trajectory of Pt-MOFs nanomotors under different H concentrations; (k) 2 O 2 The average speed of Pt-MOFs nanomotors at different H concentrations; (l) 2 O 2 Variation of the average MSD of Pt-MOFs nanomotors with time intervals under different concentrations.

[0033] Figure 3 In vitro bacterial imaging of Pt-MOFs nanomotors according to an embodiment of the present invention: (a) Typical CLSM images of Staphylococcus aureus and Pt-MOFs nanomotors after co-incubation in PBS solution or SI solution for 10, 30, and 60 minutes at 37°C, respectively; scale bar: 5 μm; (b) Relative fluorescence intensity of Staphylococcus aureus and Pt-MOFs nanomotors after co-incubation in PBS solution or SI solution for 10, 30, and 60 minutes, respectively; (c) Flow cytometry analysis of Staphylococcus aureus cells and Pt-MOFs nanomotors after co-incubation in PBS solution or SI solution for 60 minutes; (d) and (e) Typical CLSM images of Staphylococcus epidermidis and Escherichia coli at 37°C after co-incubation with Pt-MOFs nanomotors in PBS solution or SI solution for 60 minutes, respectively, scale bar: 5 μm.

[0034] Figure 4 The in vitro antibacterial activity of the Pt-MOFs nanomotors of the embodiments of the present invention: (a)-(c) the number of Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli after incubation at 37°C for 4 h at different Pt-MOFs nanomotors concentrations in SI solution; (d) typical CLSM images of Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli after incubation with Pt-MOFs nanomotors in PBS solution or SI solution at 37°C for 4 h, respectively. The bacterial cells were stained with calcein-AM (green) and PI (red) before imaging. Scale bar: 5 μm.

[0035] Figure 5In vivo fluorescence images of mice with surgical wounds infected with Staphylococcus aureus sutured with Uncoated suture, TPPE@Suture, and Pt-MOFs@Suture at predetermined time points in an example of the present invention.

[0036] Figure 6 The in vivo antibacterial properties of Pt-MOFs nanomotors in an embodiment of the present invention: (a) Schematic diagram of Pt-MOFs nanomotors treating mice with surgical wounds infected with Staphylococcus aureus; (b) Changes in mouse weight during treatment; (c) Representative images of mice in the control group with surgical wounds sutured with sutures and mice with surgical wounds infected with Staphylococcus aureus sutured with uncoated sutures, TPPE@Suture and Pt-MOFs@Suture, respectively.

[0037] Figure 7 The following are histopathological images of surgical wounds 13 days after treatment according to an embodiment of the present invention: (a) a representative image of H&E staining at day 13; (b) a tissue section stained with Masson's trichrome at day 13; (c)-(e) typical immunofluorescence staining images of anti-CK14, anti-CD31, and anti-F4 / 80 staining of cytokeratin, blood vessels, and macrophages, respectively; ImageJ software was used to quantitatively analyze the fluorescence intensity of CK 14 (f), CD31 (g), and F4 / 80 (h).

[0038] Figure 8 This is the DLS curve of the Pt nanodendrite in the embodiment of the present invention.

[0039] Fig. 9 (a) UV-visible spectrum of Pt-MOFs nanomotors in DMF solution according to the embodiment of the present invention; (b) fluorescence emission of TPPE and Pt-MOFs nanomotors in PBS at different GSH concentrations at pH 5.0, excitation wavelength: 405 nm.

[0040] Fig.10 The numbers of Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli after incubation of Pt-MOFs nanomotors with different concentrations in PBS solution at 37°C for 4 hours in the example of the present invention.

[0041] Fig.11 The examples of the present invention are changed to: Uncoated suture (a) and Pt-MOFs@Suture (b) representative SEM images; (c) fluorescence photos of TPPE@Suture and Pt-MOFs@Suture under 365nm ultraviolet light.

[0042] Fig.12The average intensity of the fluorescence signal of the surgical wound of mice infected with Staphylococcus aureus on days 1, 3, 5, and 9 after surgery is shown in the example of the present invention. The fluorescence intensity was quantified using the Caliper IVIS Lumina III system (n=3).

[0043] Fig.13 Representative images of the control group of mice with surgical wounds sutured only with sutures and the mice with surgical wounds infected with Staphylococcus aureus sutured with uncoated sutures are TPPE@Suture and Pt-MOFs@Suture, respectively.

[0044] Fig.14 These are surgical wound traces at different time points in an embodiment of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments:

[0046] Materials and strains: Escherichia coli (E. coli), Staphylococcus epidermidis (S. epidermidis), and Staphylococcus aureus (S. aureus) were purchased from the China General Microbiological Culture Collection Center (GMCC, China). The silk thread was provided by Ethicon Inc. (Ethicon, Johnson & Johnson). Hexachloroplatinic acid dihydrogen (H 2 PtCl 6 ), polyvinylpyrrolidone (PVP), glutathione (GSH), sodium hydroxide, hydrogen peroxide (30%), were purchased from Aladin reagent (Shanghai, China). Tetrakis(4-pyridylphenyl)ethylene, sodium alginate, sodium chloride (NaCl), calcium chloride (CaCl 2 ) and copper sulfate pentahydrate (CuSO 4 ·5H 2 O) was purchased from Adamas-beta (Shanghai, China). Luria-Bertani (LB) broth, LB agar, and phosphate-buffered saline (PBS) were provided by Sigma-Aldrich. All other reagents were obtained from domestic suppliers and used as received without further purification.

[0047] Animals: Female BALB / c mice (6-8 weeks, 18-20 g) were purchased from Pengyue Experimental Animal Center, Jinan, China. The animal experimental protocol was approved by the Institutional Animal Care and Use Committee of Qingdao University Medical College.

[0048] Instruments: The morphology of Pt nanoparticles and Pt-MOFs nanomotors was studied by transmission electron microscopy (TEM, HITACHI HT7700 Exalens). STEM-EDX was performed using a JEM 2100F instrument. The size, size distribution, and zeta potential of the nanoparticles were detected by DLS (Zetasizer nano ZS, Malvern). The morphological analysis of Pt-MOFs@Suture was performed on a scanning electron microscope (SEM) (Sirion 200, USA). Fluorescence images of bacteria were observed using a confocal laser scanning microscope (CLSM, Leica, SP8). UV-visible measurements and photoluminescence (PL) measurements of the samples were studied using a Cary 100 array spectrophotometer and a FluoroMax-4 fluorescence spectrometer. Flow cytometry (Beckman CytoFlex) analysis was used to quantitatively detect cell fluorescence. In vivo imaging of mice was performed using an in vivo imaging system (Caliper LifeSciences, USA).

[0049] Embodiment 1:

[0050] A Pt-MOFs nanomotor for surgical wound infection monitoring is prepared by selective anisotropic growth of Cu-based tetra(4-pyridylphenyl)ethylene (TPPE) nanoscale metal organic frameworks (Cu-MOFs) on Pt nanodendrites; the Pt nanodendrites serve as propulsion elements, and the AIE luminescent prototype MOFs serve as fluorescence generating elements and antibacterial agents. By catalyzing H 2 O 2 The reduction of Cu-MOFs releases oxygen bubbles and exhibits the ability to self-propel in infected surgical wounds; in an acidic microenvironment, overexpressed GSH can drive the dissociation of copper ions in Cu-MOFs and the protonation of TPPE, causing TPPE to aggregate on the bacterial surface.

[0051] Preparation method of Pt-MOFs nanomotors for surgical wound infection monitoring,

[0052] (1) Synthesis of Pt nanodendrites.

[0053] 82 mg H 2 PtCl 6 10mg PVP and 10mL deionized water were dissolved to prepare Pt nanodendrites. At room temperature, 5mL ascorbic acid (175mg) solution was dropped into the mixed solution. The mixed solution was then heated to 45°C and magnetically stirred at this temperature for 60min. The color of the mixed solution changed from light yellow to black, indicating that Pt nanodendrites had been synthesized.

[0054] (2) Synthesis of Pt-MOFs nanomotors.

[0055] Pvp-stabilized Pt nanodendrites were used as growth seeds. 100 μL of a methanol solution of Pvp-stabilized Pt nanodendrites (1.3 μM) was added to 4 mL of CuSO 4 ·5H 2 O (18.0 mg, 0.72 mmol) in methanol solution, vigorously stirred for 1 h, 10 mg, 0.15 mmol of TPPE was dissolved in 2 mL of tetrachloroethylene and methanol mixed solution, the volume ratio of the two was 3 / 1, and then slowly added to the above mixed solution, and vigorously stirred. The final mixture was stirred at room temperature for 6 hours, and the obtained precipitate was centrifuged at 5000 rpm for 10 minutes, washed three times with methanol, and stored in deionized water for later use.

[0056] 1. Synthesis and characterization of Pt-MOFs nanomotors

[0057] like Figure 1 As shown in Figure 1, the Pt-MOFs nanomotor consists of Pt nanodendrites as propulsion elements and AIE luminescent MOFs as fluorescence generating elements and antibacterial agents. Pt nanodendrites were chosen as the motor system because they have large roughness and active catalytic surfaces, which can improve the propulsion ability. On the other hand, the AIE luminescent source TPPE can react with copper (II) ions (Cu 2+ ) synergistically form a signal transduction probe for in situ detection of GSH levels in surgical wounds.

[0058] Pt-MOF nanomotors catalyze H 2 O 2 The reduction of Cu-MOFs releases oxygen bubbles, which show the ability to self-propel in infected surgical wounds. At the same time, under acidic microenvironment, overexpressed GSH can drive the dissociation of copper ions in Cu-MOFs and the protonation of TPPE, providing the possibility for TPPE to aggregate on the bacterial surface.

[0059] Pt-MOFs nanomotors can emit fluorescent signals to Gram-positive bacteria Staphylococcus aureus (S. aureus), Staphylococcus epidermidis (S. epidermidis) and Gram-negative bacteria Escherichia coli (E. coli) under simulated inflammatory conditions. In addition, copper ions can undergo a Fenton-like reaction to convert H 2 O 2The Pt-MOFs nanomotors are converted into highly cytotoxic hydroxyl radicals (·OH), thereby killing bacteria. In vitro experimental results show that the released copper ions have good antibacterial activity. The Pt-MOFs nanomotors were successfully used to monitor and treat surgical wounds in a mouse model of Staphylococcus aureus infection. Therefore, the Pt-MOFs nanomotors are not only potential imaging tools for monitoring surgical sites, but also powerful antibacterial agents for treating bacterial infections, providing a new design strategy for monitoring and treatment in clinical applications.

[0060] like Figure 1 As shown in a, the Janus Pt-MOFs nanomotor was synthesized by assembling two different nanodevices into one nanoparticle. Pt nanodendrites were efficiently synthesized by a self-assembly surface reduction method and verified by transmission electron microscopy (TEM) and dynamic light scattering (DLS).

[0061] Figure 2 a and b show an average diameter of 32 ± 6.1 nm, which is in good agreement with the hydrodynamic size of 37 ± 7.9 nm measured by DLS ( Figure 8 ). These nanodendrites are then coated with polyvinyl pyrrolidone (PVP) to enhance their surface hydrophilicity and promote the selective anisotropic growth of Cu-MOFs on the surface. 4 ·5H 2 The optimal amount of PVP-coated Pt nanodendrites was added to the methanol solution of O to construct a uniform mixture. The TPPE solution was slowly dripped into the mixture and stirred vigorously for 6 hours. The resulting precipitate was washed several times and collected by centrifugation. In addition, the co-assembly of Pt nanodendrites and Cu-MOFs was also studied. To confirm the successful preparation, the morphology of the Pt-MOFs nanomotors was studied using scanning electron microscopy.

[0062] like Figure 2 As shown in cf, there are Pt nanodendrite domains with high contrast on the surface of Cu-MOFs, indicating that Cu-MOFs are well developed on the surface of Pt nanodendrites and grow anisotropically. As the feed molar ratio of Pt nanodendrites / Cu-MOFs increases, the average domain size of Cu-MOFs gradually increases, from the DLS reflection range of 79 to 297 nm ( Figure 2 g). At the same time, after the growth of Cu-MOFs, the zeta potential changes from -5.47±1.2mV of Pt nanobranch to -11.4±0.71mV of Pt-MOFs nanomotor ( Figure 2h). In order to provide comprehensive evidence for the effective synthesis of Pt-MOFs nanomotors, elemental mapping by energy dispersive x-ray spectroscopy (EDS) in a scanning electron microscope was studied. The Pt element is mainly distributed on one side of the Pt-MOFs nanomotors, while the C and Cu elements are evenly distributed, showing asymmetry in composition and structure ( Figure 2 i). In addition, UV-visible (UV-vis) analysis was performed to identify the formation of Pt-MOFs nanomotors. The absorption spectrum of Pt-MOFs nanomotors observed in Pt-MOFs nanomotors exhibited a significant blue shift compared to Pt nanodendrites and TPPE ( Fig. 9 a). Finally, fluorescence spectroscopy analysis was used to better understand the formation of Pt-MOFs nanomotors. TPPE, as a hydrophobic AIE luminogen, formed aggregates in phosphate buffered saline (PBS) at pH 5.0 with strong fluorescence ( Fig. 9 b) However, the fluorescence of the synthesized Pt-MOFs nanomotors was quenched due to the electron transfer process induced by the matrix coordination in the framework. 2+ The high binding affinity of TPPE hinders the charge transfer process from TPPE to copper, resulting in the effective recovery of TPPE fluorescence.

[0063] 2. Motion analysis of Pt-MOFs nanomotors

[0064] Pt-MOFs nanomotors have a Janus structure and can catalyze H 2 O 2 Produce O 2 The self-propelled behavior of Pt-MOFs nanomotors in PBS at different fuel concentrations was observed using confocal laser scanning microscopy (CLSM), and their trajectories were analyzed using ImageJ software. 2 O 2 The excitation trajectory of Pt-MOFs nanomotors at different concentrations (0-5mM) was analyzed using ImageJ software.

[0065] Pt-MOFs nanomotors in 0 mM H 2 O 2 Under the condition of H 2 O 2 As the concentration increases, the trajectory becomes longer ( Figure 2 j). The mean square displacement (MSD) analysis was used to further study the motion characteristics of the Pt-MOFs nanomotor. As shown in Figure 21, the MSD value of the Pt-MOFs nanomotor is low and linear, which is consistent with the typical random Brownian motion. 2 O 2When , MSD increases linearly with a steeper slope, indicating that the catalytic propulsion of Pt-MOFs nanomotors depends on concentration. Figure 2 k shows that, according to the parabolic MSD equation, the Pt-MOFs nanomotors in 5 mM H 2 O 2 The average migration speed in solution reached 3.8 μm s -1 , than at 0 mM H 2 O 2 The increase in the solution was 7.4 times, which confirmed that Pt-MOFs nanomotors have the potential to become an effective carrier for biomembrane penetration.

[0066] 3. In vitro bacterial imaging

[0067] In infected tissues, bacteria colonize and proliferate rapidly, forming a unique infection microenvironment. Accordingly, the feasibility of using Pt-MOFs nanomotors for bacterial monitoring was studied under simulated infection conditions. Staphylococcus aureus, the most common pathogen of postoperative wound infection, was used as a model microorganism to study the bacterial imaging ability of Pt-MOFs nanomotors.

[0068] Gram-positive (Staphylococcus epidermidis and Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria were used as model microorganisms. First, the bacteria were cultured overnight at 37°C and then harvested by centrifugation (1500 rpm, 5 minutes). The obtained bacterial cells were washed three times with PBS. The bacteria were diluted and resuspended in PBS or simulated infection solution. A 20 μM Pt-MOFs nanomotor suspension was added to an initial density of 1×10 6 CFU mL -1 The bacteria were incubated in a PBS solution or a simulated infection (SI) solution at 37°C. The images of Staphylococcus aureus were observed using a confocal laser scanning microscope (CLSM) at predetermined time points (λex = 405 nm, λem = 450-550 nm). The bacteria were incubated with Pt-MOFs nanomotors in PBS solution or a simulated infection (SI) solution for 10, 30, and 60 minutes, respectively, at 37°C. Figure 3As shown in a and b, at 10 min, only a weak fluorescence emission of Staphylococcus aureus in the SI solution was observed in the field of view of the CLSM image, indicating that the dissociation of TPPE from the Pt-MOFs nanomotors had begun. After the Staphylococcus aureus was incubated for 30 minutes, the blue fluorescence signal emitted by the bacteria could be clearly seen. When incubated in the SI solution for 60 min, a bright blue fluorescence signal was displayed, indicating that TPPE was successfully separated from the Pt-MOFs nanomotors and aggregated on the bacterial surface. In sharp contrast, no obvious fluorescence signal was observed for the control Staphylococcus aureus in the PBS solution throughout the process, indicating that the Pt-MOFs nanomotors have the ability to track the presence of infection. Then, the changes in the fluorescence signal of Staphylococcus aureus at different time points of incubation in SI or PBS solution were monitored by flow cytometry for further quantitative verification. As Figure 3 As shown in Figure c, the fluorescence of Staphylococcus aureus incubated with Pt-MOFs nanomotors in SI solution increased significantly with the extension of incubation time. In contrast, the fluorescence change of Staphylococcus aureus was small after incubation in PBS solution for 60 min, which is consistent with the CLSM observation results. Therefore, these results indicate that the activation of the fluorescence signal of Pt-MOFs nanomotors is related to the infection microenvironment. In addition, the versatility of Pt-MOFs nanomotors was explored to monitor different strains. Figure 3 As shown in d and e, CLSM images show that Gram-positive Staphylococcus epidermidis and Gram-negative Escherichia coli can be stained by Pt-MOFs nanomotors and show bright blue fluorescence after incubation with Pt-MOFs nanomotors in SI solution for 60 min, highlighting the wide applicability of this method to monitor different strains. The experimental results further emphasize that Pt-MOFs nanomotors can be a promising candidate for monitoring surgical wound infections.

[0069] 4. In vitro antibacterial activity

[0070] Pt-MOFs nanomotors can monitor and treat infected surgical wounds by providing bacterial imaging and antibacterial therapy. Many MOFs can act as metal ion reservoirs, providing gradual release of metal ions through degradation or diffusion, and producing sustained antibacterial effects. Considering that copper ions can induce Fenton-like reactions to produce cytotoxic ·OH, the antibacterial activity of Pt-MOFs nanomotors at different concentrations against Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative (Escherichia coli) in vitro was further studied.

[0071] The colony forming units (CFU) on Burtani agar plates were used for quantitative analysis to analyze the antibacterial properties of the prepared nanomotors against bacteria. Pt-MOFs with different concentrations were treated in PBS or SI solution for 4 hours to investigate the antibacterial efficiency of the nanomotors. Antibacterial experiments were carried out using Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative bacteria (Escherichia coli) as models. At the same time, PBS and simulated infection fluid were used as incubation media for comparison. In order to study the effect of Pt-MOFs nanomotor dosage on the bacterial inhibition, a density of 1×10 7 Bacterial cells with CFU / mL were added to different concentrations of Pt-MOFs nanomotor suspensions (10, 20, and 50 μM) and incubated in PBS or simulated infection fluid for 4 h. All bacterial suspensions were then appropriately diluted, evenly spread on LB agar plates, and inoculated overnight at 37°C. Finally, the CFU of bacteria was calculated.

[0072] Live / Dead kit was used to detect different groups of bacteria. Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli were incubated with Pt-MOFs nanomotors in PBS or simulated infection solution at 37°C for 4 hours, and then centrifuged at 4°C. After the precipitate was washed with PBS, it was suspended in LB medium containing calcein-AM (green fluorescence) and propidium iodide (PI, red fluorescence) in the dark for 30 minutes. Microscopic images of bacterial cells were measured using CLSM.

[0073] like Figure 4 ac and Fig.10As shown in Figures ac, the overall survival rate of bacteria indicates that the antibacterial activity of Pt-MOFs nanomotors is dose-dependent, that is, as the concentration of Pt-MOFs nanomotors in SI solution increases, the survival rate of each bacterium decreases. Interestingly, in SI solution, both Staphylococcus aureus and Staphylococcus epidermidis are more susceptible to the concentration of Pt-MOFSs than Escherichia coli. After 20μM Pt-MOFs nanomotors were incubated in SI solution for 4h, the inhibition rates of Staphylococcus aureus and Staphylococcus epidermidis reached 85% and 99%, respectively. Further increasing the concentration of Pt-MOFs nanomotors to 80μM, the inhibition rate was close to 100%. As a relevant comparison, under the same conditions (20μM), 45% of the live bacteria were killed. Similarly, the increase in the concentration of Pt-MOFs nanomotors can enhance the inhibition rate, indicating that it has excellent broad-spectrum antibacterial properties. However, no matter Gram-positive or Gram-negative bacteria, incubated with Pt-MOFs nanomotors in PBS solution, did not show obvious antibacterial activity, and the highest antibacterial effect was only ~30%. To further confirm our results, we used live / dead bacterial staining method based on calcein-AM and propidium iodide (PI) staining to verify the survival of bacteria under different conditions. After 80μM Pt-MOFs nanomotors were incubated in SI solution for 4 hours, the three bacteria almost all emitted red fluorescence in SI solution, indicating that they were dead ( Figure 4 d). This phenomenon can be explained by the fact that Pt-MOFs nanomotors catalyze the generation of ·OH through the continuous release of copper ions in SI solution, which effectively increases the permeability of bacterial cell membranes, because PI can only enter bacterial cells with damaged cell membranes and bind to nucleic acids to produce red fluorescence. In contrast, most bacteria can be seen to have green fluorescence of calcein-AM after 4 hours of culture in PBS solution, showing negligible antibacterial activity. Overall, these results verify the great potential of Pt-MOFs nanomotors in the treatment of bacterial-related wound infections.

[0074] Embodiment 2:

[0075] A Pt-MOFs nanomotor coated suture for surgical wound infection monitoring, wherein the surface of the suture is coated with the above-mentioned Pt-MOFs nanomotor.

[0076] A method for preparing a Pt-MOFs nanomotor coated suture for surgical wound infection monitoring,

[0077] The Pt-MOFs nanomotors were coated on the surface of the nanostructured carbon foam by slurry dipping technique with sodium alginate as the fixative. Specifically, 5 ml of sodium chloride solution (0.1% w / v) was added to 5 ml of sodium alginate solution (2% w / v) and stirred overnight at room temperature. 10 mg of Pt-MOFs nanomotor was added to the above solution and magnetically stirred for 2 h to form an alginate-Pt-MOFs nanomotor solution. A 2 cm long The silk suture was immersed in the prepared alginate-Pt-MOFs nanomotor solution for 20 min and then air-dried for 10 min. This process was repeated 10 times to obtain sufficient coating on the suture surface. The coated suture was then immersed in CaCl 2 The cross-linked sutures were then immersed in a solution (4% w / v) for 1 h and washed with deionized water. Finally, the cross-linked coated sutures were dried for later use. The surface of the silk thread is coated with TPPE.

[0078] 1. Imaging of bacterial infection in vivo

[0079] In vivo fluorescence imaging experiments were performed on the full-thickness incisional wound model of BALB / c mice. The hair on the back of BALB / c mice was shaved, and a 1.5 cm longitudinal incision was made on the dorsal skin to establish a longitudinal wound model. The mice were divided into three groups: uncoated suture, TPPE@Suture suture (TPPE@Suture), and Pt-MOFs@Suture suture (Pt-MOFs@Suture), using different suture methods. To monitor bacterial infection, 50 μL of Staphylococcus aureus (1×106 cfu) was injected into the incisional wound of mice. Fluorescence imaging was performed 1, 3, 5, and 9 days after surgery. All mice were imaged at four predetermined time points using an in vivo optical imaging system (IVIS LuminaIII).

[0080] Sodium alginate, which has high biocompatibility and biodegradability, was used as an immobilization agent to coat the synthesized Pt-MOFs nanomotors on the surface of silk threads (Pt-MOFSs@Suture) by slurry impregnation. The surface of Pt-MOFSs@Suture was visualized by SEM. Compared with the uncoated suture, the SEM image of Pt-MOFSs@Suture clearly observed a smoother and more uniform morphology, indicating that the Pt-MOFs nanomotors were successfully coated on the silk threads ( Fig.11 a and b). In addition, as a control, the silk thread coated with free TPPE (TPPE@Suture) exhibited strong blue-green fluorescence under 365nm UV radiation, while no fluorescence signal was observed for Pt-MOFSs@Suture, which is consistent with the fluorescence spectrum results ( Fig.11 c).

[0081] After successfully coating Pt-MOFs nanomotors on silk surgical sutures, their clinically relevant monitoring of postoperative infection in vivo was further evaluated. A full-thickness incision wound model infected with Staphylococcus aureus was established on the right lower back of BALB / c mice, and different sutures were divided into three groups: Uncoated suture group, TPPE@Suture group, and Pt-MOFs@Suture group. 7 After 50 μL of Staphylococcus aureus containing cfu was injected into the incision wound of mice, the infection status of the surgical wound was monitored at predetermined time points using an in vivo optical imaging system (IVIS Lumina III). Figure 5 As shown, obvious fluorescence signals were observed at the surgical suture points in the TPPE@Suture group 1 day after surgery, while no fluorescence accumulation was observed at the surgical wounds in the Uncoated suture group and the Pt-MOFs@Suture group. The detected fluorescence signals of the TPPE@Suture group are believed to be generated by the TPPE aggregated in the TPPE@Suture coating. However, unlike the Uncoated suture group and the TPPE@Suture group, the fluorescence intensity of the surgical wound site sutured by Pt-MOFs@Suture continued to increase with time and reached a maximum value 5 days after surgery, which can be explained by the successful dissociation of TPPE from the Pt-MOFs nanomotors and their aggregation on the bacterial surface in the surgical wound tissue, indicating the occurrence of infection. At the same time, the quantitative results also showed that the changes in the average fluorescence intensity of the infected tissues of mice were consistent with those presented by the IVIS images ( Fig.12 ). In particular, on the fifth day after surgery, the relative signal intensity was at least 2.6 times higher than that of the Uncoated suture group and the TPPE@Suture group. The above results indicate that Pt-MOFSs@Suture can monitor surgical wounds through activation of the infection microenvironment.

[0082] 2. Antibacterial properties in the body

[0083] To further confirm the antibacterial activity of Pt-MOFs nanomotors in vivo, the effect of Pt-MOFs@Suture on the wound model of Staphylococcus aureus infection in mice was evaluated. A 1.5 cm longitudinal full-thickness incision was made on the back skin of BALB / c mice, and then they were randomly divided into a control group, an Uncoated suture group, a TPPE@Suture group, and a Pt-MOFs@Suture group (n=5). Afterwards, according to the experimental design, the mice were treated as follows Figure 6a. First, all mice were intraperitoneally injected with cyclophosphamide to eliminate leukocytes and provide a susceptible tissue environment for bacterial infection. The control group only sutured the incision skin without any treatment. The mice in the Uncoated suture group, TPPE@Suture group, and Pt-MOFs@Suture group were sutured with different sutures and inoculated with 100 μL Staphylococcus aureus (10 8 cfu mL -1 ) infection. The topographic features of the wound healing process were captured by taking photos every 2 days. Fig.13 and Figure 6 As shown in c, on the first day after surgery, slight edema was observed around the wound surface in the uncoated suture group, TPPE@Suture group, and Pt-MOFs@Suture group, indicating bacterial infection at the wound site. Compared with the control group, the edema area in the Uncoated suture group, TPPE@Suture group, and Pt-MOFs@Suture group increased significantly on the third day, and ulcers of varying degrees appeared on the wound surface on the fifth day. Black scabs appeared at the wound site in the Pt-MOFs@Suture group on the fifth day, indicating that the infected tissue began to repair itself. On the 11th day after surgery, the wound surface in the Pt-MOFs@Suture group gradually recovered, the scabs fell off, and new skin regenerated, while larger scabs still appeared in the Uncoated suture group and TPPE@Suture group. At the same time, traces of the wound bed were also used to intuitively demonstrate the healing process of the wounds in each group ( Fig.14 ). In addition, the weight changes of each mouse were monitored during the wound healing process to detect health status. Figure 6 As shown in b, except for the control group mice whose weight increased steadily throughout the experiment, the mice in the Uncoated suture group, TPPE@Suture group, and Pt-MOFs@Suture group all showed significant weight loss during the infection period. Importantly, the weight of the mice in the Pt-MOFs@Suture group increased rapidly as the wound healed. These results indicate that Pt-MOFs nanomotors can indeed significantly inhibit bacteria in the infected area of ​​the wound.

[0084] In order to further and more accurately evaluate the quality of wound healing, a series of skin tissue staining of the incision wound was performed on the 13th day after surgery, including hematoxylin and eosin (H&E) staining and Masson's trichrome staining. Figure 7 As shown in a, new capillaries and skin growth were observed in the control group and Pt-MOFs@Suture group, while no epidermal tissue was found in the Uncoated suture group and TPPE@Suture group. Compared with the Uncoated suture group and TPPE@Suture group, the Pt-MOFs@Suture group had less inflammatory infiltration and more newly regenerated hair follicles. In addition, collagen deposition and arrangement, as important indicators of the wound healing process, were studied by Masson's trichrome staining. Figure 7As shown in b, the collagen fiber deposition in the Pt-MOFs@Suture group was significantly higher than that in the Uncoated suture group and the TPPE@Suture group, the latter of which had insufficient collagen expression. In addition, the Pt-MOFs@Suture suture wound showed uniform accumulation of collagen fibers and intact skin structure, similar to the control group, indicating that Pt-MOFs nanomotors may play an effective role in accelerating wound healing. In order to evaluate the re-epithelialization of wound tissue, immunofluorescence staining of cytokeratin 14 (CK 14) of wound tissue was performed. On the 13th day after surgery, the thickness of the green epithelium in the wound of the Pt-MOFs@Suture group was as thin as that of the control group, while no cytokeratin layer was observed in the uncoated suture group and the TPPE@Suture group, further proving that the Pt-MOFs nanomotors promoted rapid and complete re-epithelialization ( Figure 7 c and f). Angiogenesis is also an important factor in evaluating the progress of wound healing. Immunofluorescence staining was used to analyze the typical angiogenesis-related marker CD31. Figure 7 As shown in d and g, it can be clearly seen that the expression of CD31 in granulation tissue increased significantly, indicating that the density of new blood vessels formed in the Pt-MOFs@Suture group was greater than that in the uncoated suture group and the TPPE@Suture group on day 13. In a parallel experiment, immunofluorescence staining of macrophage F4 / 80 was performed to evaluate the inflammatory state of the wound. Figure 7 As shown in e and h, the red fluorescence intensity of F4 / 80 in the Uncoated suture and TPPE@Suture groups was significantly higher, indicating the presence of bacterial infection, which is consistent with the results of H&E staining. In contrast, the fluorescence signal of the Pt-MOFs@Suture group was much lower, indicating that the Pt-MOFs nanomotors can effectively inhibit Staphylococcus aureus infection in vivo. In summary, these results indicate that Pt-MOFs nanomotors exhibit excellent performance in inhibiting bacterial infection and promoting wound healing.

[0085] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.

Claims

1. A Pt-MOFs nanomotor for surgical wound infection monitoring, characterized in that: The Cu-based tetra(4-pyridylphenyl)ethylene (TPPE) nanoscale metal-organic frameworks (Cu-MOFs) were prepared by selective anisotropic growth on Pt nanodendrites. The Pt nanodendrites serve as propulsion elements, and the AIE luminescent prototype MOFs serve as fluorescence generating elements and antibacterial agents.

2. The Pt-MOFs nanomotor for surgical wound infection monitoring according to claim 1, characterized in that: By catalyzing the reduction of H2O2 and releasing oxygen bubbles, it exhibits the ability to self-propel in infected surgical wounds; in an acidic microenvironment, overexpressed GSH can drive the dissociation of copper ions in Cu-MOFs and the protonation of TPPE, causing TPPE to aggregate on the bacterial surface.

3. The method for preparing the Pt-MOFs nanomotor for surgical wound infection monitoring according to any one of claims 1 to 2, characterized in that: (1) Synthesis of Pt nanodendrites; (2) Synthesis of Pt-MOFs nanomotors: The methanol solution of PVP-stabilized Pt nanodendrites was added to the methanol solution of CuSO4·5H2O and stirred vigorously for 1 hour. 10 mg, 0.15 mmol of TPPE was dissolved in a mixed solution of tetrachloroethylene and methanol, with a volume ratio of tetrachloroethylene to methanol solution of 3:1, and then slowly added to the above-prepared mixed solution and stirred at room temperature for 6 hours. After the precipitate was centrifuged, it was washed with methanol to obtain the Pt-MOFs nanomotor, which was stored in deionized water.

4. The method for preparing the Pt-MOFs nanomotor for surgical wound infection monitoring according to claim 3, characterized in that: The synthesis steps of the Pt nanodendrites include: H2PtCl6 and PVP were dissolved in deionized water. At room temperature, ascorbic acid solution was dropped into the mixed solution. The mixed solution was heated to 45°C and magnetically stirred at this temperature for 60 min. The color of the mixed solution changed from light yellow to black, indicating the synthesis of Pt nanodendrites.

5. The method for preparing the Pt-MOFs nanomotor for surgical wound infection monitoring according to claim 3, characterized in that: The volume ratio of the methanol solution of PVP-stabilized Pt nanodendrites to the methanol solution of CuSO4·5H2O was 1:40; The concentration of the methanol solution of CuSO4·5H2O is 0.18 mol / L, and the concentration of the methanol solution of the pvp-stabilized Pt nanodendrites is 1.3 μM.

6. The method for preparing the Pt-MOFs nanomotor for surgical wound infection monitoring according to claim 4, characterized in that: The mass ratio of H2PtCl6, PVP and ascorbic acid is 8.2:1:17.

5. The concentration of H2PtCl6 was 8.2 mg / ml, the concentration of PVP was 1 mg / ml, and the concentration of ascorbic acid was 35 mg / ml.

7. A Pt-MOFs nanomotor coated suture for surgical wound infection monitoring, characterized in that: The surface coating of the suture is the Pt-MOFs nanomotor described in any one of claims 1-2.

8. The method for preparing a Pt-MOFs nanomotor coated suture for surgical wound infection monitoring according to claim 7, characterized in that: Sodium chloride solution was added to sodium alginate solution, stirred at room temperature overnight, Pt-MOFs nanomotor was added to the solution, and magnetic stirring was performed for 2 h to form alginate-Pt-MOFs nanomotor solution; Will The silk suture was immersed in the alginate-Pt-MOFs nanomotor solution for 20 min and air-dried for 10 min. After repeating 10 times, the coated suture was immersed in a CaCl2 solution for cross-linking and continued to be immersed for 1 h. After washing with deionized water, the cross-linked coated suture was dried to obtain the Pt-MOFs nanomotor coated suture.

9. The method for preparing a Pt-MOFs nanomotor coated suture for surgical wound infection monitoring according to claim 8, characterized in that: The mass fraction of the sodium chloride solution is 0.1%, the mass fraction of the sodium alginate solution is 2%, and the volume ratio of the sodium chloride solution to the sodium alginate solution is 1:

1.

10. The method for preparing a Pt-MOFs nanomotor coated suture for surgical wound infection monitoring according to claim 8, characterized in that: The mass fraction of CaCl2 solution is 4%.

Citation Information

Patent Citations

  • Nanometer motor composite material and preparation method and application thereof

    CN117653747A

  • Method for preparing and purifying metal organic framework material fixed with NANO platinum and use thereof

    WO2019174260A1